NTA CSIR UGC NET SET JRF lecturership Chemical Sciences - Preeti Gupta; Tomar, Aditya Sharma, Naveen (New Delhi Arihant, 2025)
Chemical Periodicity and Chemistry of Main Group Elements, Chemical Bonding and Structure of Molecules, Acid-Base Chemistry, s-Block Elements, p-Block Element, p-Block Elements-I (Group 13), The p-Block Element-II, Noble Gases, d-Block Elements or Transition Elements, Coordination Chemistry, Inner Transition Elements, Organometallic Compounds, Analytical Chemistry, Bioinorganic Chemistry, Coordination Compounds, Part-II, Nuclear Chemistry, Quantum Mechanics or Wave Mechanics, Atomic Structure and Quantum Theory, Chemical Bonding and Diatomics, Molecular Symmetry and Group Theory, Molecular Spectroscopy, Thermodynamics, Statistical Thermodynamics, Electrochemistry, Chemical Kinetics, Surface Chemistry, Solid State, Data Analysis, IUPAC Nomenclature of Organic Compounds, Stereochemistry, Aromaticity, Organic Reaction Mechanism and Reactive Intermediates, Common Named Reactions and Rearrangements, Organic Transformations and Reagents, Concept in Organic Synthesis and Asymmetric Synthesis, Pericyclic Reactions, Photochemistry, Heterocyclic Compounds, Chemistry of Natural Products, Interdisciplinary Topics, Sample Questions Provided on CSIR Website, Solved Paper 2024
Keywords: Chemical Sciences